Rapid Detection and Antimicrobial Susceptibility Testing of Pathogens Using AgNPs-Invertase Complexes and the Personal Glucose Meter - Zheng, Laibao; Shen, Yunqiu; Dong, Wenjia; Zheng, Chaochuan; Zhou, Ruolan; Lou, Yong-Liang (Frontiers in Bioengineering and Biotechnology, 2022)
Rapid detection of pathogens and assessment of antimicrobial susceptibility is of great importance for public health, especially in resource-limiting regions. Herein, we developed a simple, portable, and quantitative detection method for bacteria using AgNPs-invertase complexes and PGMs without multiple washing and rinsing steps. In the presence of bacteria, the invertase could be released from AgNPs-invertase complexes where its enzyme activity of invertase was inhibited. Then, the enzyme activity of invertase was restored and could convert sucrose into glucose measured by a commercially PGM. There was a good linear relationship between PGM signal and concentration of E. coli (from 1×102 cfu/mL to 1×107 cfu/mL) or S. aureus (from 1×103 cfu/mL to 1×107 cfu/mL), with the limit of detection of 2.99 cfu/mL and 7.59×102 cfu/mL respectively. Our proposed biosensor was proved to be a rapid and reliable method for antimicrobial susceptibility testing within 4 h with consistent results of MIC testing.